MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK MELALUI KEGIATAN MELIPAT KERTAS PADA ANAK USIA 4-5 TAHUN DI TK. AL-FALAH DESA NAUMBAI KECAMATAN KAMPAR - Neli Susanti; Zulkifli Zulkifli; Daviq Chairilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on field observations of the fine motor skills of the students have not developed optimally. So that should be the implementation of the activities of folding paper. This study aims to determine the increase finely hatched ability of children through paper folding activity in children aged 4-5 years in kindergarten Al-Falah Village Naumai Kampar District. This research is a type of research that use or classroom action research (PTK) is conducted in two cycles , Each cycle consists of planning, action planning, observation / evaluation and reflection. The subjects were kindergartner Group A, amounting to 18 people. The research data obtained through observation and data analysis were performed quantitatively. The results showed lower paper folding activity may improve fine motor skills of kindergarten children Group A. It can be seen from the increase in the average percentage of the fine motor skills of children in the first cycle of 37.2 2% were currently on criteria began to develop (MB) and experienced an increase of 43% in the second cycle into 53.24 which are in the developing kritria expectations (BSH). Thus, activity of paper folding can improve fine motor skills of children Group A TK Al-Falah Village Naumai Kampar District.Keywords: Fine motor skill, Folding Paper